2013
DOI: 10.1523/jneurosci.0032-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

A Sensitive Period for GABAergic Interneurons in the Dentate Gyrus in Modulating Sensorimotor Gating

Abstract: Developmental perturbations during adolescence have been hypothesized to be a risk factor for the onset of several neuropsychiatric diseases. However the physiological alterations that result from such insults are incompletely understood. We investigated whether a defined perturbation during adolescence affected hippocampus-dependent sensorimotor gating functions, a proposed endophenotype in several psychiatric diseases, most notably schizophrenia. The developmental perturbation was induced during adolescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 58 publications
3
22
0
Order By: Relevance
“…The slope of the regression line was used to estimate the total number of GAD‐positive neurons per dentate gyrus from profile counts for all of the mice. The average number of GAD‐positive neurons per hippocampus in control mice was comparable to that estimated in one previous study (Guo, Koshizaki, et al, ), but higher than that in another (Wei et al, ). The average number of GAD‐positive neurons per dentate gyrus in epileptic mice (5660 ± 70) was 72% of that in controls (7860 ± 300, p < 0.001, Mann–Whitney rank sum test) (Figure c).…”
Section: Resultssupporting
confidence: 85%
“…The slope of the regression line was used to estimate the total number of GAD‐positive neurons per dentate gyrus from profile counts for all of the mice. The average number of GAD‐positive neurons per hippocampus in control mice was comparable to that estimated in one previous study (Guo, Koshizaki, et al, ), but higher than that in another (Wei et al, ). The average number of GAD‐positive neurons per dentate gyrus in epileptic mice (5660 ± 70) was 72% of that in controls (7860 ± 300, p < 0.001, Mann–Whitney rank sum test) (Figure c).…”
Section: Resultssupporting
confidence: 85%
“…4C), and that GABA agonists injection into the DG of these mice (i.e., substitution of reduced GABA inputs) recovers their PPI deficits (Fig. 4D) (Guo et al, 2013). Taken altogether, an excessive excitatory activation (excess output of immature newborn neurons and/or less of GABAergic inhibition in the DG) might affect NAc activity and dopamine release, eventually causing disruption of normal PPI in Fabp7 and Fabp7/5 KO mice.…”
Section: Fabps and Animal Behaviormentioning
confidence: 79%
“…The physiological implications for these increases are unknown. Other studies have found that GABAergic neuronal circuitry is vulnerable during adolescence, with effects persisting into adulthood (Guo et al, 2013). …”
Section: Discussionmentioning
confidence: 99%